Self-Regulated Learning on Students’ Oral Presentation Performance in Academic Speaking Class (RETAIN, 2020)
Abstract Self-regulated learning (SRL) has been proven to have positive effects on students’ learning outcomes. Since oral presentation performance skills have benefits for students’ academic and career fields, this study aimed to investigate students’ self-regulated learning through oral presentation performance. Additionally, 20 English education students in one of the academic speaking classes in UNESA were selected. This study was under Zimmerman cyclical theory of self-regulated learning, which involves three phases; forethought, performance, and reflection. Hence, this study was to investigate how the students were planning, monitoring, and also evaluating their oral presentation performance. This study was conducted after the students have finished their first presentation performance. Afterward, an interview was given to obtain data from students’ responses. The result of the study showed that most of the students have goals to decrease anxiety, and verbal learning style was highly used to learn the material of presentation. Therefore, the students read their notes, which is one of the ways to self control their speech from any disruptions during the presentation performance. Besides, replay the video recording, and self-motivating helped them to evaluate the progress of oral presentation performance. Keywords: Self-Regulated Learning, Oral Presentation Performance